ГЕНЕРАТИВНЫЕ МЕДИА И ИХ СУБЪЕКТ В ПЕРСПЕКТИВЕ КРИТИЧЕСКОЙ ТЕОРИИ И ПСИХОАНАЛИЗА. - Константюк, Виктория (Topos (18150047), 2025)
This article explores how generative media and artificial intelligence reshape subjectivity, perception, and communication in the (post) digital age. Drawing on critical theory and psychoanalysis — particularly the works of Mark Andrejevic, Slavoj Žižek, Bernard Stiegler, John Black, and others — the article analyzes how algorithmically-driven media affect the dynamics of desire, knowledge, and autonomy. Special attention is given to the dialectic between subjectivity and algorithmic regulation, the psychoanalytic concept of the “desire not to know,” and the transformation of creativity under conditions of automated content production. The discussion uncovers the ideological functions of generative media, showing how AI does not merely mediate perception but actively participates in the structuring of the unconscious. Tracing the historical evolution of media as both technological and symbolic systems, the article argues for a critical re-evaluation of the socio-political and epistemological implications of AI-generated content. Ultimately, it challenges the presumed neutrality of generative technologies, foregrounding their role in the reproduction of power, desire, and subject formation.